2020
DOI: 10.1016/j.critrevonc.2020.103059
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus infection and immune system: An insight of COVID-19 in cancer patients

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 66 publications
1
42
0
1
Order By: Relevance
“…These were tested for two gene targets: ORF1ab and N. According to accumulating data, analyzing the genome of the SARS-CoV-2, ORF and N genes represent the most specific target for its identification [9,10]. ORF1ab is highly presumptive for the presence of SARS-CoV-2; while the N gene might be detected even in other coronavirus infections [1,9,10].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These were tested for two gene targets: ORF1ab and N. According to accumulating data, analyzing the genome of the SARS-CoV-2, ORF and N genes represent the most specific target for its identification [9,10]. ORF1ab is highly presumptive for the presence of SARS-CoV-2; while the N gene might be detected even in other coronavirus infections [1,9,10].…”
Section: Methodsmentioning
confidence: 99%
“…According to accumulative data regarding analysis of the SARS-CoV-2 genome, the ORF and N genes represent the most specific targets for its detection [9 , 10] . The ORF1ab gene is highly presumptive for the presence of SARS-CoV-2, whereas the N gene might be detected even in other coronavirus infections [1 , 9 , 10] . The amplification curve of the ORF1ab gene suggested that 1 case was positive for SARS-CoV-2, whereas the amplification curve of the N gene suggested a presumptive positive case of SARS-CoV-2 (because the amplification curve of the N gene might be related to another coronavirus infection).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations